2018
DOI: 10.1126/sciimmunol.aat2738
|View full text |Cite
|
Sign up to set email alerts
|

Chemical disruption of the pyroptotic pore-forming protein gasdermin D inhibits inflammatory cell death and sepsis

Abstract: Dysregulation of inflammatory cell death is a key driver of many inflammatory diseases. Pyroptosis, a highly inflammatory form of cell death, uses intracellularly generated pores to disrupt electrolyte homeostasis and execute cell death. Gasdermin D, the pore-forming effector protein of pyroptosis, coordinates membrane lysis and the release of highly inflammatory molecules, such as interleukin-1β, which potentiate the overactivation of the innate immune response. However, to date, there is no pharmacologic mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
319
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(363 citation statements)
references
References 29 publications
10
319
0
2
Order By: Relevance
“…GSDMD was also demonstrated to play a key role in the pathogenesis of steatohepatitis by controlling cytokine secretion, and Gsdmd knockout mice exhibit decreased severity of steatosis and inflammation in a high‐fat diet‐induced model of non‐alcoholic steatohepatitis (Xu et al , ). Pharmacologic inhibition of GSDMD by necrosulfonamide also was efficacious in sepsis models (Rathkey et al , ). Finally, antabuse (disulfiram), a drug used to treat alcohol addiction, was shown to inhibit GSDMD pore formation and IL‐1β secretion in human and mouse cells, and LPS‐induced septic death and IL‐1β secretion in mice (preprint: Hu et al , ).…”
Section: Pharmacological Targeting Of Inflammasomesmentioning
confidence: 99%
See 1 more Smart Citation
“…GSDMD was also demonstrated to play a key role in the pathogenesis of steatohepatitis by controlling cytokine secretion, and Gsdmd knockout mice exhibit decreased severity of steatosis and inflammation in a high‐fat diet‐induced model of non‐alcoholic steatohepatitis (Xu et al , ). Pharmacologic inhibition of GSDMD by necrosulfonamide also was efficacious in sepsis models (Rathkey et al , ). Finally, antabuse (disulfiram), a drug used to treat alcohol addiction, was shown to inhibit GSDMD pore formation and IL‐1β secretion in human and mouse cells, and LPS‐induced septic death and IL‐1β secretion in mice (preprint: Hu et al , ).…”
Section: Pharmacological Targeting Of Inflammasomesmentioning
confidence: 99%
“…Sulfonylurea-based compounds Glyburide (+) Specific for NLRP3 inflammasomes; significantly delays LPS-induced mortality (Lamkanfi et al, 2009) (À) High dosage required (Marchetti et al, 2014); cardiovascular side effects (Riddle, 2003) TBI (Simard et al, 2012) Ischemic stroke (Simard et al, 2012) CP-412,245 and CP-424,174 (+) Oral administration of CP-424,174 selectively blocks IL-1 production in mice (Perregaux et al, 2001) CRID1 and CRID2 (À) No in vivo evidence MCC950 (also known as CRID3 or CP-456,773) ( +) NLRP3 inflammasome specific (Coll et al, 2015); inhibits NLRP3 activation by all known stimuli ( (Rathkey et al, 2018) diet-induced model of non-alcoholic steatohepatitis . Pharmacologic inhibition of GSDMD by necrosulfonamide also was efficacious in sepsis models (Rathkey et al, 2018). Finally, antabuse (disulfiram), a drug used to treat alcohol addiction, was shown to inhibit GSDMD pore formation and IL-1b secretion in human and mouse cells, and LPS-induced septic death and IL-1b secretion in mice (preprint: Hu et al, 2018).…”
Section: Nlrp3 Inflammasome Inhibitorsmentioning
confidence: 99%
“…Although GSDMD is rapidly activated in response to MSU crystals, it was shown to be dispensable for MSU crystal–mediated IL‐1β release and cell death both in vitro and in vivo . Interestingly, necrosulfonamide (NSA), a GSDMD inhibitor, can hinder IL‐1β release in response to MSU crystals, suggesting a role for NSA in blocking inflammasome activation pathway upstream of GSDMD …”
Section: Urate‐induced Immune Programmingmentioning
confidence: 99%
“…73 Interestingly, necrosulfonamide (NSA), a GSDMD inhibitor, can hinder IL-1β release in response to MSU crystals, suggesting a role for NSA in blocking inflammasome activation pathway upstream of GSDMD. 73,74 Pyroptosis ultimately functions as a defense mechanism against infection by clearing out pathogens. When innate immune cells sense danger signals, they become activated, produce inflammatory cytokines, and can undergo pyroptosis, augmenting inflammation, thus contributing to the development of adaptive responses.…”
Section: Inflammasome Activationmentioning
confidence: 99%
“…We found that pretreatment with the cytoprotective agent glycine had no effect on Prdx4 release ( Fig 5F). In contrast, both blockage of the pyroptotic pore-forming protein gasdermin D (GSDMD) by its direct chemical inhibitor necrosulfonamide (NSA) (Rathkey et al, 2018) and inhibition of extracellular vesicle shedding by GW4869 (Kosaka et al, 2010;Mittelbrunn et al, 2011) significantly lowered Prdx4 secretion. Together, these data suggest that Prdx4 is not passively lost in response to inflammasome activation and its release involves GSDMD-dependent mechanisms and also the formation of extracellular vesicles.…”
Section: Prdx4 Is Secreted Upon Activation Of the Nlrp3 Inflammasomementioning
confidence: 99%